CO2-in-PEG emulsion-templating synthesis of poly(acrylamide) with controllable porosity and their use as efficient catalyst supports. Issue 63 (16th June 2016) - Xue, Zhimin; Chang, Weihong; Cheng, Yan; Liu, Jing; Li, Jian; Zhao, Wancheng; Mu, Tiancheng
Abstract : Porous poly(acrylamide)s nanoparticles prepared from CO2 -in-PEG emulsions have high catalytic activity for benzene hydrogenation reaction. Abstract : CO2 -in-PEG emulsions were made with Pluronic 104 at different CO2 pressure. In these emulsions, porous poly(acrylamide)s (PAM) nanoparticles around 250 nm were prepared. The nano-sized metal Ru particles were loaded on the porous PAM, which have much higher catalytic activity for benzene hydrogenation reaction compared to commercial Ru/C catalyst. More importantly, the drop size of internal phase CO2 and the pore diameter of as-prepared PAMs can be simply tuned by changing the pressure of CO2 .